De quel genre littéraire l’hagiographie est-elle le nom chez Michel de Certeau ? - Agnès Guiderdoni (Les Dossiers du GRIHL)
Michel de Certeau wrote and published three times, in three different places, one almost identical text dealing with hagiography: in two editions of the Encyclopædia Universalis (1971 and 1985) and as a chapter in L'écriture de l'histoire in 1975. Certeau mentionned that hagiography is first and foremost a literary genre and treated it in a relatively elliptical manner; it gave a definition of it difficult to embrace, precisely because of its inclusion in the literary field. We will try to clarify this text and this definition, which are difficult to grasp, using especially other texts written by Certeau, to finally try to answer that question: which is finally the name of hagiography as a literary genre?